Optimizing Horizontal Collaboration in Logistics with Neutrosophic Z-Number Decision Models - Phi-Hung Nguyen; Lan-Anh Thi Nguyen; The-Vu Pham; Hong-Quan Le; Thu-Hoai Thi Nguyen; Tra-Giang Vu; Huong-Giang Hoang Le (Neutrosophic Sets and Systems)
Horizontal collaboration (HC) has emerged as a strategic approach to improve efficiency, sustainability, and competitive advantage while reducing CO2 emissions in supply chain operations. Despite its potential, HC implementation faces significant challenges, including trust management, strategic alignment, and decision-making complexities. This study proposes an integrated methodology that combines the Delphi technique and the DEMATEL framework, enhanced by Neutrosophic Z-number (NZN) theories, to identify and prioritize critical success factors (CSFs) influencing HC. A case study in Vietnam validates the robustness and practical applicability of the proposed model. The findings highlight economic factors—such as financial stability, data sharing, and innovation adoption—as key drivers of successful HC. Additionally, social factors, including organizational culture and conflict resolution, are found to be intricately linked to economic performance. Environmental factors emphasize the critical role of green practices and resource optimization. This research provides actionable insights for logistics companies and policymakers aiming to promote effective HC, thereby advancing logistics efficiency and sustainability in Vietnam and other developing economies. The proposed framework also offers a valuable foundation for future research and practical innovations in optimizing logistics collaboration.